Fikih Mayoritas versus Fikih Minoritas: Melacak Akar Konflik Sosial atas Nama Syari’at - Ahmad Imam Mawardi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
The basic character of fiqh is essentially relative, flexible and elastic. This character is visible when fiqh must adapt to social and cultural conditions of geographic areas that far from the birthplace of Islam. However, the basic character of fiqh is denied by some Muslim groups. They want to uniform fiqh according to their their interpretation that are considered more authentic and closer to the middle east fiqh format, centers the birth of Islam. The implication then is the